2020
DOI: 10.15252/embj.2019104185
|View full text |Cite
|
Sign up to set email alerts
|

Timeless couples G‐quadruplex detection with processing by DDX 11 helicase during DNA replication

Abstract: Regions of the genome with the potential to form secondary DNA structures pose a frequent and significant impediment to DNA replication and must be actively managed in order to preserve genetic and epigenetic integrity. How the replisome detects and responds to secondary structures is poorly understood. Here, we show that a core component of the fork protection complex in the eukaryotic replisome, Timeless, harbours in its C‐terminal region a previously unappreciated DNA‐binding domain that exhibits specific b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 91 publications
(137 reference statements)
1
43
0
Order By: Relevance
“…Interestingly, in this study, Timeless has been demonstrated to bind various types of G4s with high affinity through a conserved C-terminal α-helical domain. Of note, in the DT40 cell system, co-depletion of both DDX11 and FANCJ has an additive effect on the loss of the epigenetic marks at the BU-1 site, indicating that these two DNA helicases might operate in independent parallel pathways important for G4 resolution at the replication fork [ 40 ]. In line with these results, in a very recent paper by the laboratory of Job de Lange and Rob Wolthuis on novel WABS cases, it has been reported that loss of both DDX11 and FANCJ has additive effects in DNA damage accumulation in various human cell lines following treatment with Pyridostatin, a G4-stabilizer, or mitomycin C, a DNA cross-linker [ 33 ].…”
Section: Cellular Functions Of Ddx11mentioning
confidence: 99%
“…Interestingly, in this study, Timeless has been demonstrated to bind various types of G4s with high affinity through a conserved C-terminal α-helical domain. Of note, in the DT40 cell system, co-depletion of both DDX11 and FANCJ has an additive effect on the loss of the epigenetic marks at the BU-1 site, indicating that these two DNA helicases might operate in independent parallel pathways important for G4 resolution at the replication fork [ 40 ]. In line with these results, in a very recent paper by the laboratory of Job de Lange and Rob Wolthuis on novel WABS cases, it has been reported that loss of both DDX11 and FANCJ has additive effects in DNA damage accumulation in various human cell lines following treatment with Pyridostatin, a G4-stabilizer, or mitomycin C, a DNA cross-linker [ 33 ].…”
Section: Cellular Functions Of Ddx11mentioning
confidence: 99%
“…DDX11 helicase activity along its Fe–S domain are essential for unwinding DNA replication forks ( 12 , 25 , 26 ). Moreover, the interaction between DDX11 and Timeless facilitates normal replication fork speed and the processing of G4 secondary structures ( 8 , 13 , 16 ). To inquire on the activities/interactions of DDX11 facilitating cell survival in response to chemotherapy-induced lesions, we stably complemented U2OS DDX11 KO by ectopically overexpressing different DDX11 variants, namely DDX11-WT (wild type), DDX11-K50R (helicase dead), DDX11-R263Q (Fe–S domain mutated), and DDX11-KAE (lacking interaction with the Timeless-Tipin complex) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, DDX11 is required for the survival of advanced melanomas ( 9 ), lung adenocarcinomas ( 10 ), and hepatocellular carcinomas ( 11 ). In terms of molecular functions, DDX11 interacts physically with the replication fork component Timeless to assist replisome progression and to facilitate epigenetic stability at G-quadruplex (G4) structures and sister chromatid cohesion ( 12 16 ). Notably, DDX11 also contributes along 9–1-1, Fanconi anemia factors, and SMC5/6 to prevent cytotoxicity of PARPi and ICLs ( 17 20 ).…”
mentioning
confidence: 99%
“…In line with these findings, Sale and Pellegrini laboratories have recently reported that in DT40 cells the direct interaction between DDX11 and Timeless is critical for epigenetic mark inheritance at the BU-1 chromosomal locus. This latter harbors a stable G4 structure located in front of the BU-1 gene promoter that was proposed to be resolved by the combined action of chicken DDX11 and Timeless during passage of the replication fork [ 46 ]. Interestingly, in this study the authors also reported the identification and structural analysis of a novel Timeless C-terminal α-helical domain that could bind various kinds of G4 structures with high affinity.…”
Section: Functions Of Ddx11 In Dna Repair and Replication Fork Promentioning
confidence: 99%
“…Understanding how DDX11, Timeless (together with the other components of the fork–protection complex), PARP-1 and the replicative DNA helicase (the CMG complex) cooperate at a stalled replisome to remove the G4 roadblock represents a very fascinating experimental challenge. Of note, in the DT40 cell system, co-depletion of both DDX11 and FANCJ had an additive effect on the loss of the epigenetic marks at the BU-1 site indicating that these two DNA helicases might operate in independent parallel pathways important for G4 resolution at the replication fork [ 46 ]. These findings are consistent with a very recent study by the Job de Lange and Rob Wolthuis laboratory, where the effects of G4 stabilization on proliferation, chromosomal anomalies and DNA damage were analyzed in various DDX11-depleted cell lines (including lines derived from WABS patients) [ 17 ].…”
Section: Functions Of Ddx11 In Dna Repair and Replication Fork Promentioning
confidence: 99%